The Effects of Tax Wedges on Hours Worked and Unemployment in Sweden - Thomas, Alun (IMF Working Papers; Working Paper ;, 1998)
The paper investigates the relationship between labor taxation and unemployment in Sweden by estimating a labor market model that includes a wage-setting locus and labor demand and supply relationships. The study simulates the effect of a 1 percentage point increase in the payroll tax and in total tax rates. The increase in the payroll tax pushes up labor costs by about 1\2 percent over a 5-10 year time horizon. Hours worked fall by 0.5 percent and the unemployment rate rises by 0.3 percentage point. The increase in total tax rates generates a similar result. Therefore, it appears that increases in taxes have adversely affected employment and unemployment in Sweden.